2019
DOI: 10.3390/su11174701
|View full text |Cite
|
Sign up to set email alerts
|

Household Waste Sorting and Engagement in Everyday Life Occupations After Migration—A Scoping Review

Abstract: The aim of this scoping review was to gain an overview of the current state of the literature on the engagement in waste sorting post migration from an occupational perspective, in the light of two aspects sustainability efforts currently face: Increased human migration and environmental degradation. Both the resource recovery and occupational science literature were reviewed and analyzed. However, despite the current lack on studies on how migrants' transition into waste sorting schemes at the household level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 76 publications
2
23
0
6
Order By: Relevance
“…Yet, the population studied here included international students, which indicates that the perceived importance of waste sorting is not restricted to the context of Sweden or local social norms. In fact, this finding is in line with other studies that have shown that people with an immigration background display the same attitudes towards recycling as nonimmigrants (e.g., [26,27]) and that the perception of the benefits of waste sorting is the main trigger for waste sorting behavior among ethnically diverse people in Sweden [28]. However, currently there is insufficient knowledge on the role of attitudes, culture, traditions and language in waste sorting behavior [26].…”
Section: Discussion Of the Theoretical Contextsupporting
confidence: 86%
“…Yet, the population studied here included international students, which indicates that the perceived importance of waste sorting is not restricted to the context of Sweden or local social norms. In fact, this finding is in line with other studies that have shown that people with an immigration background display the same attitudes towards recycling as nonimmigrants (e.g., [26,27]) and that the perception of the benefits of waste sorting is the main trigger for waste sorting behavior among ethnically diverse people in Sweden [28]. However, currently there is insufficient knowledge on the role of attitudes, culture, traditions and language in waste sorting behavior [26].…”
Section: Discussion Of the Theoretical Contextsupporting
confidence: 86%
“…The social pressure that people may perceive from the broader society influences moral norms regarding participation in waste sorting [64], given that people might look at the habits of the broader society before choosing to behave in specific ways [91]. However, subjective norms also center around how that engagement takes place while recognizing the role that culture may play in shaping the significance and expectation of the participation in sorting [23].…”
Section: Subjective Normmentioning
confidence: 99%
“…Learning from people who made sorting their waste an everyday routine can aid tailoring campaigns aimed at moral norms. It can do so by providing knowledge and raising awareness about how individual action can improve the environment and human well-being locally and globally [23].…”
Section: Moral Normmentioning
confidence: 99%
See 2 more Smart Citations